Thermal Model of Induction Machine and its Practical Verification - Toman, Marek (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2016)
This article deals with making of thermal models of electric machines using so-called thermal network. The first part of this article describes reasons why thermal models of electric machine should be used. In the second part the heat transfer basics and thermal network basics are described. The last part is focused on simulation of a thermal network of a specific induction machine and its verification of correct functionality by measurements.
Keywords: Temperature; thermal model; heating curve; induction machine